AGRIPRENEUR SUSTAINABILITY STRATEGIES AND FINANCIAL PERFORMANCE OF SMALL-SCALE FARMERS IN UASIN-GISHU COUNTY, KENYA - Kebenei, Michael; Mathenge , Paul; Mwangi, Elias (European Journal of Business and Strategic Management, 2021)
Purpose: The purpose of this study was to examine agripreneur sustainability strategies and financial performance of SMEs in Uasin Gishu County with a specific interest of small-scale farmers in Uasin Gishu County. Materials and Methods: A descriptive survey research design was adopted in the study. The target population comprised of 1,397 small scale farmers in Uasin-Gishu County. A sample size of 140 respondents was selected using simple random sampling technique. Questionnaire was the key data collection instrument. The collected data was analyzed using quantitative and qualitative approaches of analysis. Statistical Package for Social Services version 21 was used to summarize the quantitative data into frequencies and percentages. The summarized information was presented using figures, tables and pie charts. Results: From the analysis, the following key findings were made: there is a strong positive association between financial performance and innovation (r=.219*), pro-activeness (r=.505), risk taking (.256), and networking (r=.410). The coefficient of determination indicates that 32.7% of variation of financial performance is explained by agripreneurship sustainability strategies such as innovation, pro-activeness, risk-taking and networking. It is concluded that innovation, pro-activeness, risk-taking and networking affect the financial performance of Small scale farmers in Uasin Gishu County. Unique contribution to theory, practice and policy: The study recommends that there is a need for regular training opportunities to be provided to the small scale farmers. Organizations in the agricultural sector and government ministries should focus on training farmers on entrepreneurship as a sustainable course for the business growth. Education policies in the country need to be reviewed to integrate agripreneurship as a course and more resource provided to encourage it among students in learning institutions. There is also a need for agricultural seminars to be organized within the county for the small scale farmers. There is need for further research to be conducted to assess the other factors that may be affecting the financial performance of small scale farmers.